Discomfort with uncertainty: Is testing for Brugada syndrome in the neonatal period warranted? - Vazquez, Michelle N.; Simson, Gabrielle Gold-von (Journal of Pediatric Genetics, 2013)
Brugada syndrome (BrS) is rare genetic disorder, which manifests as syncope or sudden death caused by polymorphic ventricular tachycardia. Diagnosis is based on symptoms and characteristic electrocardiography findings. Identification of mutations in SCN5A support the diagnosis, but the yield is low. According to experts, BrS patients with a history of cardiac arrest should have insertion of an automatic implantable cardiac defibrillator and asymptomatic patients can be managed conservatively. Treatment challenges occur in patients with “intermediate” clinical characteristics and in populations where there is paucity of data such as with neonates and children. We discuss the case of a woman with BrS who is faced with decision challenges in the postpartum period. Should her newborn have testing? When? Will deferment of testing impose an unreasonable uncertainty due to delay of diagnosis? Or conversely, will premature workup impose an unnecessary intervention?
Keywords: Brugada syndrome; genetic testing; neonatal